Microstructure and magnetization study of Li and Li–Zn ferrites synthesized by an electron beam; Materials Chemistry and Physics; Vol. 302 - Lysenko E. N. Elena Nikolaevna; Vlasov V. A. Vitaliy Anatolievich; Nikolaev E. V. Evgeny Vladimirovich; Surzhikov A. P. Anatoly Petrovich; Korobeynikov M. V. Mikhail Vasiljevich (2023, 2023)
Title screen